Quality of life and side effect assessment in South African patients undergoing androgen deprivation therapy - Baladakis, Dr John-Demetrios (My University, 2018)
Quality of life and side effect assessment in South African patients undergoing androgen deprivation therapy Background: In South Africa, prostate cancer is the second most commonly diagnosed cancer and accounts for 13% of male cancer related deaths. Androgen deprivation therapy (ADT) is a mainstay in the management of metastatic prostate cancer. Despite broadening indications and widespread use of ADT, it is not an innocuous treatment. The aim of this study was to determine the impact of ADT on the quality of life (QOL) and common side effects experienced by a subset of South African patients with prostate cancer. Methods A prospective, contextual, descriptive study was performed. The European Organisation for Research and Treatment of Cancer quality of life questionnaire (EORTC QLQ30) was used in conjunction with the QLQ- PR 25, to assess QOL and disease-specific impact. Results: ADT was most commonly prescribed for patients with metastatic prostate cancer 86 (56.9%). Continuous ADT was the favoured regime with a mean duration of 41.5 ± 31.2 months. Only 11 (7.2%) of the patients underwent bilateral orchiectomy. New onset hypercholesterolaemia occurred in 71 (46.7%) of the population and was associated with a continuous ADT regime 60 (87.0%). Patients had overall good QOL for the five functional scales although prostate specific symptoms had relatively high symptom scores. Only 99 (66.0%) of the study population reported ongoing sexual activity. A significant difference was found for overall QOL between patients on intermittent ADT and those on continuous ADT (p= 0.0107). Conclusion: Several pertinent issues have been highlighted with regards to the side effect profile in this population and the need for ongoing screening and management, including a patientcentered approach.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Urology, Johannesburg 2018